Partitioning and availability of sediment–bound metals following final sewage effluent release to a lowland river. (4th August 2014) - Bubb, J.M.; Lester, J.N.
A simple partitioning scheme was used to assess the partitioning and behaviour of copper, cadmium, iron, lead and manganese within the surface waters and sediments of the River Yare, Norfolk, UK, following the discharge of final effluent to the water course from municipal sewage treatment works (STW). Sewage effluent discharges were shown to increase metal concentrations and complexation capacities in receiving waters, but the tidal nature of the river meant that surface water monitoring could not accurately pinpoint the contamination source or the main metal partitioning trends. Sediments formed a more stable base on which to perform contaminant studies: these revealed that metals discharged from the STW rapidly accumulated in bottom deposits in relative stable chemical forms.